Risk of Gastrointestinal Bleeding with Rivaroxaban: A Comparative Study with Warfarin - Muhammed Sherid; Samian Sulaiman; Salih Samo; Husein Husein; Ruth Tupper; Charles Spurr; Humberto Sifuentes; Subbaramiah Sridhar (Gastroenterology Research and Practice)
Introduction. The risk of gastrointestinal (GI) bleeding with rivaroxaban has not been studied extensively. The aim of our study was to assess this risk in comparison to warfarin. Methods. We examined the medical records for patients who were started on rivaroxaban or warfarin from April 2011 to April 2013. Results. We identified 300 patients (147 on rivaroxaban versus 153 on warfarin). GI bleeding occurred in 4.8% patients with rivaroxaban when compared to 9.8% patients in warfarin group (p=0.094). GI bleeding occurred in 8% with therapeutic doses of rivaroxaban (>10 mg/d) compared to 9.8% with warfarin (p=0.65). Multivariate analysis showed that patients who were on rivaroxaban for ≤40 days had a higher incidence of GI bleeding than those who were on it for >40 days (OR = 2.8, p=0.023). Concomitant use of dual antiplatelet agents was associated with increased risk of GI bleeding in the rivaroxaban group (OR = 7.4, p=0.0378). Prior GI bleeding was also a risk factor for GI bleeding in rivaroxaban group (OR = 15.5). Conclusion. The incidence of GI bleeding was similar between rivaroxaban and warfarin. The risk factors for GI bleeding with rivaroxaban were the first 40 days of taking the drug, concomitant dual antiplatelet agents, and prior GI bleeding.